Physical properties and morphology of crosslinked polyurethane synthesized from para‐phenylene diisocyanate and polyether polyol. Issue 37 (31st May 2017) - Huan, Yan; Liu, Jia; Wang, Jie; Wu, Fan; Yang, Xiaoniu
ABSTRACT: A series of crosslinked polyurethanes (PUs) were synthesized from para ‐phenylene diisocyanate, 2‐(hydroxymethyl)‐2‐ethyl propane‐1, 3‐diol (TMP), and butane‐1, 4‐diol as the hard segments and poly(oxytetramethylene glycol) as the soft segments. The effects of TMP on the physical properties and microphase structure of the PUs were studied with dynamic mechanical analysis, Fourier transform infrared–attenuated total reflection spectroscopy, small‐angle X‐ray scattering (SAXS), and mechanical testing. We found that the storage modulus, hydrogen bonding with carbonyl groups, SAXS intensity, and hysteresis values decreased with increasing TMP; this indicated that the degree of microphase separation decreased with the increasing crosslinking density introduced by TMP. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45241. Abstract :